Cortisol excess in chronic kidney disease – A review of changes and impact on mortality - Sagmeister, Michael S.; Harper, Lorraine; Hardy, Rowan S. (Frontiers in Endocrinology, 2023)
Chronic kidney disease (CKD) describes the long-term condition of impaired kidney function from any cause. CKD is common and associated with a wide array of complications including higher mortality, cardiovascular disease, hypertension, insulin resistance, dyslipidaemia, sarcopenia, osteoporosis, aberrant immune function, cognitive impairment, mood disturbances and poor sleep quality. Glucocorticoids are endogenous pleiotropic steroid hormones and their excess produces a pattern of morbidity that possesses considerable overlap with CKD. Circulating levels of cortisol, the major active glucocorticoid in humans, are determined by a complex interplay between several processes. The hypothalamic-pituitary-adrenal axis (HPA) regulates cortisol synthesis and release, 11β-hydroxysteroid dehydrogenase enzymes mediate metabolic interconversion between active and inactive forms, and clearance from the circulation depends on irreversible metabolic inactivation in the liver followed by urinary excretion. Chronic stress, inflammatory states and other aspects of CKD can disturb these processes, enhancing cortisol secretion via the HPA axis and inducing tissue-resident amplification of glucocorticoid signals. Progressive renal impairment can further impact on cortisol metabolism and urinary clearance of cortisol metabolites. Consequently, significant interest exists to precisely understand the dysregulation of cortisol in CKD and its significance for adverse clinical outcomes. In this review, we summarise the latest literature on alterations in endogenous glucocorticoid regulation in adults with CKD and evaluate the available evidence on cortisol as a mechanistic driver of excess mortality and morbidity. The emerging picture is one of subclinical hypercortisolism with blunted diurnal decline of cortisol levels, impaired negative feedback regulation and reduced cortisol clearance. An association between cortisol and adjusted all-cause mortality has been reported in observational studies for patients with end-stage renal failure, but further research is required to assess links between cortisol and clinical outcomes in CKD. We propose recommendations for future research, including therapeutic strategies that aim to reduce complications of CKD by correcting or reversing dysregulation of cortisol.